Moko Taura - Takuira-Leaf, Tirakahurangi (Te Kaharoa, 2020)
Mapihi sat underneath the pretty pink flowers on the camellia tree. She used the cover to hide away and avoid helping her koro move the boxes on the trailer into the old raggedy house her māmā recently reclaimed. She didn’t know why her māmā made a big fuss about this house; the squatters previously living here didn’t take much care of it; it was run down and ugly.